Trans-cis inter-conversion of blankophur BBU - Ung, Paul Y.
Fluorescent brightening agents are aromatic substances which give colorless solutions but which are strongly fluorescent when in aqueous solutions. The greenish blue to reddish violet fluorescence emitted by the brightener appears as a brilliant white shade when combined with the yellow color inherent of the substrate.